Development of Animated Video-Based Educational Media on the Use of Traditional Medicinal Plants for Family Health - Magfirah Rasyid; Aswal Salewangeng; Yusmar Yusuf (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to develop an animated video-based educational medium on the use of traditional medicinal plants for family health and to evaluate the product validity and initial user responses. The study employed a Research and Development (R&D) approach based on the Thiagarajan 4D development model. The research stages included define, design, develop, and limited disseminate. Product validity was assessed by four validators, consisting of two subject-matter experts and two media experts, while the user response test involved 72 respondents aged 18–50 years in Ternate City. Data were collected using validation questionnaires and user response questionnaires based on a Likert scale, and were then analyzed descriptively in percentage form. The results showed that the material validity reached 92% and the media validity reached 91%, both of which were categorized as very valid. User responses obtained an average score of 81.11%, indicating that the medium was positively received and feasible for use as a supporting educational tool. These findings indicate that the developed animated video met the criteria for content feasibility, language quality, visual presentation, and ease of use at the limited testing stage. Therefore, the developed medium can be used as a means of family health education.